Dampak Reputasi Underwriter, Ukuran Perusahaan dan Financial Leverage Terhadap Underpricing Saham Pada Saat IPO (Studi Kasus Pada Perusahaan Sub-Sektor Teknologi) - Oniesca Martha; Ardiansyah Japlani; Karnila Ali (Jurnal Manajemen DIVERSIFIKASI, 2026)
In the process of issuing shares to the Stock Exchange or known as Initial Public Offering (IPO), underpricing often occurs, which is a phenomenon where the initial share offering price is lower than the closing price in the secondary market. This study aimed to examine the impact of several factors that affect stock underpricing when companies conduct IPOs on the Indonesia Stock Exchange. The time span of this research was 2019 to 2022. The factors studied in this study were Underwriter Reputation, Company Size and Financial Leverage. This research used a quantitative approach, where data were collected and analyzed statistically. This research data analysis used multiple linear regression analysis. The sampling method used purposive sampling with several criteria in accordance with the research objectives and obtained 6 companies as samples from a population of 9 companies. The results showed that partial testing showed variable Underwriter Reputation had a negative and significant effect on Underpricing. While variables Company Size and Financial Leverage had no significant effect on Underpricing and simultaneously. Simultaneous testing of the variables of Underwriter Reputation, Company Size and Financial Leverage had no effect on Underpricing.